The Preferred Learning Modes of Online Graduate Students - Kuboni, Olabisi (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
This paper reports on a research project aimed at identifying the preferred approaches to learning of mature students in an online graduate programme. Interest in this issue was generated by the positions taken by certain theorists who argue for less focus on interaction and collaboration as the basis for learning in the online environment. They contend that the learner as an individual should be acknowledged. A questionnaire, operationalizing four learning modes, was used to solicit responses from graduate students. The modes were independent learning, instrumental learning, interactive learning, and collaborative learning. Factor analysis confirmed the four as student preferred learning modes. In addition it allowed for the emergence of specific attributes of each. While instrumental learning emerged as a strong factor, the most dominant construct emerging was a dimension of collaborative learning. It is envisaged that the findings of the study can inform the design of online teaching-learning strategies for this category of students.